Implementasi Peran Pemuda dalam Memimpin Gerakan Zero Waste - Ridho, Muhamad Syahadad; Arya Taufiqurrahman, Muhammad Rafif (Review of International Relations, 2024)
The zero waste movement has become a global concern in an effort to overcome or reduce environmental problems, especially waste. With this problem, youth or students are one of the main forces in leading the zero waste movement. This research was conducted to examine the implementation of the role of youth in leading the zero waste movement through community approaches, education, and social action to encourage environmentally friendly practices. The research method used is descriptive analysis by collecting data and obtained directly from the object under study from the community, student groups, field observations and the media. The results showed that the role of youth is very effective in mobilizing and sensitizing the community to participate in the zero waste movement through various ways and various activities. However, things that still need to be overcome are such as lack of public awareness, lack of government support and role, and limited resources. Therefore, awareness and joint efforts from various parties are needed to support the role of youth in carrying out the zero waste movement which is useful for creating a clean environment and future life.